2021
DOI: 10.1097/pep.0000000000000799
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Learning in Pediatric Physical Therapist Education: Faculty and Student Perceptions

Abstract: This study aimed to describe use of experiential learning (EL) with children in entry-level doctor of physical therapy programs. Experiential learning is a recommended educational strategy for building physical therapy knowledge and skills. Subjects: Faculty teaching pediatric content in accredited doctor of physical therapy programs was recruited; 106 responded. Students representing 20 participating programs were also invited to participate; 23 responded. Methods: Participants received an online questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Doctor of physical therapy educators who had completed an initial questionnaire on the use of EL with children were asked to participate in a follow-up interview 8. This initial questionnaire asked participants how many hours of EL with children are included in their DPT program.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Doctor of physical therapy educators who had completed an initial questionnaire on the use of EL with children were asked to participate in a follow-up interview 8. This initial questionnaire asked participants how many hours of EL with children are included in their DPT program.…”
Section: Methodsmentioning
confidence: 99%
“…This initial questionnaire asked participants how many hours of EL with children are included in their DPT program. Based on prior research, purposive sampling was used to identify educators from programs that used a low quantity (5 hours and less) or a high quantity (13.5 hours and more) of EL with children, from programs with diverse student cohort sizes, and from different geographic regions 8. A total of 18 educators ultimately participated in the individual semistructured interviews: 9 from programs using a high quantity and 9 from programs using a low quantity of EL with children.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiential learning is a “... unique and nonnegotiable dimension of excellence in pediatric physical therapy education”6 that provides opportunities for DPT students to have direct engagement with a child and the family 7,8. In DPT pediatric education, there is variability in the implementation of experiential learning opportunities (ELOs) 10. Common implementation strategies of ELOs include engagement with community partners, laboratory activities or classroom interactions with children and families, and high-fidelity human simulation 11–13…”
Section: Introductionmentioning
confidence: 99%
“…Despite this apparent importance, variability in implementation exists across DPT programs 3. In a recent survey exploring the use of EL with children, pediatric faculty from 80 DPT programs reported that students engaged in a mean of 12.4 hours of EL with children (range: 0-40 hours) and 8.9 hours specifically with children who have participation restrictions (range: 0-38 hours) 4. Only 61.7% of the faculty respondents were moderately or extremely satisfied with the quantity of EL with children in their program 4…”
Section: Introduction and Purposementioning
confidence: 99%